Genetic association between sow longevity and social genetic effects on growth in pigs - Hong, Joon Ki (Asian-Australasian journal of animal sciences, 2019)
OBJECTIVE: Sow longevity is important for efficient and profitable pig farming. Recently, there has been an increasing interest in social genetic effect (SGE) of pigs on stress-tolerance and behavior. The present study aimed to estimate genetic correlations among average daily gain (ADG), stayability (STAY), and number of piglets born alive at the first parity (NBA1) in Korean Yorkshire pigs, using a model including SGE